White toner
By reasonably formulating the work functions of white pigments and inorganic fine particles in the white toner, the problem of uneven charge in the prior art is solved, and image stability and high-quality printing are achieved under different environments.
Patent Information
- Application Number
- CN201980079925.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-03
- Filing Date
- 2019-11-27
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2039-11-27
AI Technical Summary
The existing white toners are unevenly charged when the use environment changes, resulting in unstable image density and fogging, and lack of follow-up.
A white toner containing a binder resin, a white pigment and inorganic fine particles is used. The work function of the white pigment is 5.80 eV or more and 6.10 eV or less, the work function of the inorganic fine particles is 6.15 eV or more, and the content of the white pigment is 15.0 mass. The content of inorganic fine particles is 0.1 parts by mass or more, and the production of the melt kneading method ensures charging uniformity and stability.
The charging uniformity and image stability are achieved under different usage environments, the occurrence of image defects is suppressed, and high-quality white toner is provided.
Smart Images

Figure CN113168124B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a toner for use in electrophotography, electrostatic recording, electrostatic printing and toner jetting processes. Background Art
[0002] As an image forming apparatus using an electrophotographic method, in the prior art, an image forming apparatus is proposed which forms a toner image on a transfer material using not only color toners such as yellow, magenta, cyan and black toners but also a white toner having white color. For example, by color printing on color paper other than white paper or printing with a white toner as a base layer, the color tone of an image formed by the color toner is made vivid, thereby enabling various expressions.
[0003] Various white pigments have been proposed for use as white toners. For example, Patent Document 1 proposes the use of at least one selected from aluminum oxide, titanium oxide, magnesium oxide, and calcium oxide as a white pigment. However, white pigments may be positively charged and make the toner non-uniformly charged when used as a negative toner. This will result in a wide charge distribution. Such a wide charge distribution may cause fogging in the non-image portion, resulting in a lack of followability of the charge in response to changes in its use environment and a lack of image density stability just after the power is turned on.
[0004] In addition, Patent Document 2 proposes to use two kinds of titanium oxide particles to improve whiteness and light resistance. However, even in this method, the charging stability in the use environment is not sufficient. As a result, the image density changes or fogging occurs as the use environment changes.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Publication No. H07-082243
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 2012-128008 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] The present invention aims to provide a white toner that can solve the above problems. Specifically, the present invention aims to provide a white toner that has excellent charging uniformity and can stably print high-quality images regardless of the use environment.
[0011] Solutions for solving problems
[0012] The present invention relates to a white toner, comprising white toner particles containing a binder resin, a white pigment and inorganic fine particles, wherein the work function of the white pigment is 5.80 eV or more and 6.10 eV or less, the content of the white pigment is 15.0 parts by mass or more and 60.0 parts by mass or less relative to 100 parts by mass of the binder resin, and the work function of the inorganic fine particles is 6.15 eV or more.
[0013] Effects of the Invention
[0014] According to the present invention, it is possible to provide a white toner which has excellent charging uniformity and can stably print high-quality images regardless of the use environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] [ Figure 1 ] is a schematic diagram of a surface modification device that can be used in the present invention.
[0016] [ Figure 2 ] is a schematic diagram of a unit for powder measurement.
[0017] [ Figure 3 ] is a schematic diagram illustrating the surface analysis method. DETAILED DESCRIPTION
[0018] Hereinafter, embodiments for carrying out the present invention will be described in detail.
[0019] The present inventors have found that, in the presence of a white pigment having a predetermined work function and inorganic fine particles having a predetermined work function in toner particles, the positive chargeability of the white pigment can be neutralized to improve the charge uniformity of the entire toner.
[0020] In the white toner according to the present invention, toner particles containing a binder resin contain 15.0 parts by mass or more and 60.0 parts by mass or less of a white pigment having a work function of 5.80 eV or more and 6.10 eV or less relative to 100 parts by mass of the binder resin.
[0021] If the content of the white pigment in the toner particles is within this range, sufficient coloring power can be obtained and charging of the toner can be controlled more uniformly.
[0022] The white toner according to the present invention contains inorganic fine particles having a work function of 6.15 eV or more.
[0023] The inorganic fine particles having such a work function and the white pigment having a work function of 5.80 eV or more and 6.10 eV or less, if contained in the toner particles at the same time, can neutralize the positive charge to stabilize the charge. As a result, the occurrence of image defects can be suppressed even in long-term use. The inorganic fine particles are contained in the toner particles in an amount preferably of 0.1 parts by mass or more and 15.0 parts by mass or less, more preferably of 0.5 parts by mass or more and 10.0 parts by mass or less, relative to 100 parts by mass of the binder resin. In particular, a content of 4.0 parts by mass or more and 9.0 parts by mass or less is preferred.
[0024] The inorganic fine particles preferably include both particles dispersed in the interior of the white toner particles (wherein the interior of the white toner particles corresponds to an area on the center side greater than 0.50 μm from the particle surface) and particles present on the surface of the white toner particles. The amount of inorganic fine particles present in the interior of the white toner particles is preferably 0.1 parts by mass or more and 2.5 parts by mass or less relative to 100 parts by mass of the binder resin. The amount of inorganic fine particles present on the surface of the white toner particles is preferably 2.5 parts by mass or more and 7.0 parts by mass or less relative to 100 parts by mass of the inorganic fine particles before treatment. The presence of inorganic fine particles on the surface of the white toner particles can reduce the influence of temperature and humidity caused by changes in the use environment, and obtain higher charging uniformity.
[0025] In the present invention, the white pigment is preferably a white pigment selected from the group consisting of titanium oxide fine particles, calcium carbonate fine particles, zinc oxide fine particles, aluminum oxide fine particles, aluminum hydroxide fine particles and magnesium oxide fine particles. These white pigments have high coloring power and are suitable for use in negatively chargeable toners from the viewpoint of charging characteristics.
[0026] The inorganic fine particles are preferably silica fine particles. Silica fine particles can improve the dispersibility of the white pigment in the toner particles without impairing the whiteness.
[0027] Next, each component contained in the white toner according to the present invention will be described.
[0028] [Binder resin]
[0029] Any binder resin may be used without limitation, and the polymers or resins listed below may be used.
[0030] For example, the following can be used: homopolymers of styrene and its substituents such as polystyrene, polyparachlorostyrene and polyvinyltoluene; styrene-based copolymers such as styrene-parachlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylate copolymers, styrene-methacrylate copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers and styrene-acrylonitrile-indene copolymers; poly(vinyl chloride), phenolic resins, natural modified phenolic resins, natural resin modified maleic acid resins, acrylic resins, methacrylic resins, poly(vinyl acetate), silicone resins, polyesters, polyurethanes, polyamides, furan resins, epoxy resins, xylene resins, poly(vinyl butyral), terpene resins, coumarone-indene resins and petroleum resins.
[0031] Among these resins, polyester or a hybrid resin of polyester and a vinyl resin is preferably used from the viewpoint of low-temperature fixing property and controllable charging property.
[0032] Examples of the acid component and the alcohol component used for preparing the polyester include divalent or higher alcohols and divalent or higher carboxylic acids, as well as divalent or higher carboxylic acid anhydrides and divalent or higher carboxylic acid esters.
[0033] Examples of divalent or higher alcohols include alkylene oxide adducts of bisphenol A such as polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene (3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene (2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene (2.0)-polyoxyethylene (2.0)-2,2-bis(4-hydroxyphenyl)propane and polyoxypropylene (6)-2,2-bis(4-hydroxyphenyl)propane, ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-Butanediol, neopentyl glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polybutylene glycol, sorbitol, 1,2,3,6-hexanetetraol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane and 1,3,5-trimethylolbenzene.
[0034] Among them, the alcohol preferably used is an aromatic diol. The proportion of the aromatic diol in all alcohol monomer components forming the polyester is preferably 80 mol% or more.
[0035] On the other hand, examples of acid monomer components such as divalent or higher carboxylic acids, divalent or higher carboxylic acid anhydrides and divalent or higher carboxylic acid esters include aromatic dicarboxylic acids such as phthalic acid, isophthalic acid and terephthalic acid, or their anhydrides; alkyl dicarboxylic acids such as succinic acid, adipic acid, sebacic acid and azelaic acid, or their anhydrides; succinic acid substituted by an alkyl or alkenyl group having a carbon number of 6 to 18, or its anhydride; and unsaturated dicarboxylic acids such as fumaric acid, maleic acid and citraconic acid, or their anhydrides.
[0036] Among them, the acid monomer component preferably used is a polycarboxylic acid such as terephthalic acid, succinic acid, adipic acid, fumaric acid, trimellitic acid, pyromellitic acid and benzophenonetetracarboxylic acid, and anhydrides thereof.
[0037] From the viewpoint of the stability of the triboelectric charge, the acid value of the polyester is preferably above 1 mgKOH / g and below 20 mgKOH / g. The acid value can be controlled within this range by adjusting the monomer type or the amount of the monomers used for the resin. Specifically, the acid value can be controlled by adjusting the ratio or molecular weight of the alcohol and acid during the preparation of the resin. Alternatively, the acid value can be controlled by performing an ester polycondensation followed by a reaction of a terminal alcohol with a polyacid monomer such as trimellitic acid.
[0038] In the case of a hybrid resin of polyester and a vinyl resin, a bi-reactive monomer reactive with these resin components may be used.
[0039] [wax]
[0040] The white toner particles may contain wax. Any wax may be used without limitation. Examples of waxes include the following: hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes; oxides of hydrocarbon waxes such as oxidized polyethylene waxes, or block copolymers thereof; waxes containing fatty acid esters as a main component such as carnauba wax; and waxes obtained by partially or completely deoxygenating fatty acid esters such as deacidified carnauba wax. Other examples of waxes include the following: saturated linear fatty acids such as palmitic acid, stearic acid and montanic acid; unsaturated fatty acids such as brazileic acid, eleostearic acid and octadecatetraenoic acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, wax alcohol and myricol; polyols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid or montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, wax alcohol or myricol; fatty acid amides such as linoleic acid amide, oleamide and lauric acid amide; saturated Fatty acid bisamides; unsaturated fatty acid amides such as ethylenebisoleamide, hexamethylenebisoleamide, N,N'-dioleyl adipamide and N,N'-dioleyl sebacic acid amide; aromatic bisamides such as meta-xylene distearamide and N,N'-distearylisophthalic acid amide; fatty metal salts (commonly referred to as metal soaps) such as calcium stearate, calcium laurate, zinc stearate and magnesium stearate; waxes obtained by grafting aliphatic hydrocarbon waxes with vinyl monomers such as styrene or acrylic acid; partial esterification products of fatty acids and polyols such as monoglyceride of behenic acid; and methyl ester compounds having hydroxyl groups obtained by hydrogenation of vegetable oils and fats.
[0041] Among these waxes, hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax are preferred in order to improve low-temperature fixability and resistance to fixation wrapping.
[0042] The content of the wax used is preferably 0.5 to 20 parts by mass relative to 100 parts by mass of the binder resin. From the viewpoint of the storability and high-temperature offset property of the toner, a wax having a maximum endothermic peak at a peak temperature of 50 to 110° C. in an endothermic curve obtained as a result of measurement with a differential scanning calorimeter (DSC) is preferred.
[0043] [Charge control agent]
[0044] The white toner particles may contain a charge control agent as required. Known charge control agents can be used. In particular, a metal compound of an aromatic carboxylic acid which is colorless and can rapidly charge the toner and stably maintain a fixed charge amount is preferred.
[0045] Examples of negative charge control agents include salicylic acid metal compounds, naphthoic acid metal compounds, dicarboxylic acid metal compounds, polymer compounds having sulfonic acid or carboxylic acid on the side chain, polymer compounds having esterification products of sulfonates or sulfonic acids on the side chain, polymer compounds having esterification products of carboxylates or carboxylic acids on the side chain, boron compounds, urea compounds, silicon compounds, and calixarene. The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 to 10 parts by mass relative to 100 parts by mass of the binder resin.
[0046] [External additives]
[0047] The white toner according to the present invention may further contain an external additive to improve fluidity or adjust the triboelectric charge amount as necessary.
[0048] Preferred external additives are inorganic fine particles such as silica fine particles, titanium oxide fine particles, aluminum oxide fine particles, and strontium titanate fine particles. In addition, the inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.
[0049] The external additive is preferably used in an amount of 0.1 to 5.0 parts by mass relative to 100 parts by mass of the toner particles.
[0050] [Carrier]
[0051] The white toner according to the present invention is preferably mixed with a magnetic carrier and used as a two-component developer because stable images are obtained over a long period of time.
[0052] Conventionally known magnetic carriers can be used, and examples thereof include surface-oxidized iron powder, unoxidized iron powder, particles of metals such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese and rare earth elements, particles of their alloys, oxide particles, magnetic substances such as ferrite, and resin carriers in which the magnetic substance is dispersed, which include a magnetic substance and a binder resin that can maintain the magnetic substance in a dispersed state (so-called resin carriers).
[0053] [Production method]
[0054] The white toner according to the present invention can be produced by a conventionally known production method such as an emulsification aggregation method, a melt kneading method or a dissolution suspension method, etc. From the viewpoint of dispersibility of the raw material, a kneading pulverization method is preferred.
[0055] In the kneading pulverization method, first, the raw materials are mixed. In the raw material mixing step, a predetermined amount of materials constituting white toner particles are weighed, blended and mixed. The materials include a binder resin, a white pigment, inorganic fine particles and other optional components such as a charge control agent, wax and a colorant. Examples of mixing equipment include a double cone mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer and a mechanical hybridizer (manufactured by NIPPON COKE & ENGINEERING CO., LTD.). Preferably, the amount of inorganic fine particles to be mixed here corresponds to the amount of only inorganic fine particles present in the interior of the white toner particles (wherein the interior of the white toner particles corresponds to the central side area greater than 0.50 μm from the particle surface). Specifically, the inorganic fine particles are preferably used in an amount of 0.1 parts by mass or more and 2.5 parts by mass or less relative to 100 parts by mass of the binder resin.
[0056] Next, the mixed material is melt-kneaded to disperse the raw materials other than the binder resin in the binder resin. In the melt-kneading step, an intermittent kneading machine such as a pressure kneading machine or a Banbury mixer or a continuous kneading machine can be used. Single screw or twin screw extruders are mainly used because their advantage is that they can be produced continuously. Examples of extruders include KTK-type twin screw extruders (manufactured by Kobe Steel, Ltd.), TEM-type twin screw extruders (manufactured by TOSHIBA MACHINE CO., LTD.), PCM kneaders (manufactured by Ikegai Corp.), twin screw extruders (manufactured by KCK KK), co-kneaders (manufactured by Buss-SMS-Canzler GmbH), and Kneadex (manufactured by NIPPON COKE & ENGINEERING CO., LTD.). In addition, the resin composition obtained by melt-kneading can be rolled with a double roller, etc., and can be cooled with water, etc. in the cooling step.
[0057] In the next step, in the pulverizing step, the cooled product of the resin composition is pulverized to a desired particle size. In the pulverizing step, the cooled product is coarsely pulverized with, for example, a grinder such as a crusher, a hammer mill or a cutting mill, and then, for example, finely pulverized with a CRYPTRON system (manufactured by Kawasaki Heavy Industries, Ltd.), a Super Rotor (manufactured by NISSHINENGINEERING INC.), a turbo grinder (manufactured by FREUND-TURBO CORPORATION) or a jet mill.
[0058] Subsequently, the pulverized product is classified as necessary using a classifier such as an inertial classification type elbow jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP separator (manufactured by Hosokawa Micron Corporation) or FACULTY (manufactured by Hosokawa Micron Corporation), or a sifter to obtain toner particles.
[0059] After pulverization, the toner particles may be optionally subjected to surface treatment such as spheroidization treatment using a hybrid system (manufactured by Nara Machinery Co., Ltd.), a MECHANO FUSION system (manufactured by Hosokawa Micron Corporation), a FACULTY (manufactured by Hosokawa Micron Corporation), or a Meteorainbow MR type (manufactured by Nippon Pneumatic Mfg. Co., Ltd.).
[0060] In particular, in the present invention, preferably, additives such as inorganic fine particles and resin particles are added to the surface of white toner particles and dispersed by mixing; in this dispersed state, the white toner particles are surface-treated with hot air to fix the additives to the surface of the white toner particles. Preferably, the mixing amount of the inorganic fine particles corresponds to the amount of only the inorganic fine particles present on the surface of the white toner particles. Specifically, the inorganic fine particles are preferably used in an amount of 2.5 parts by mass or more and 7.0 parts by mass or less relative to 100 parts by mass of the toner particles before treatment.
[0061] In the present invention, the white toner particles can be used, for example Figure 1 The surface treatment device shown in the embodiment performs surface treatment with hot air and can be optionally classified to obtain a white toner. Figure 1 To illustrate the surface treatment.
[0062] The mixture quantitatively supplied by the raw material quantitative supply unit 1 is introduced into the introduction pipe 3 vertically provided to the raw material supply unit by the compressed gas adjusted by the compressed gas adjustment unit 2. The mixture passing through the introduction pipe is uniformly dispersed by the conical protrusion member 4 provided in the central part of the raw material supply unit, introduced into the supply pipes 5 radially provided in eight directions, and then introduced into the processing chamber 6 where the mixture is heat-treated.
[0063] At this time, the flow of the mixture supplied to the processing chamber is restricted by a restriction unit 9 for restricting the flow of the mixture, which is provided in the processing chamber. To this end, the mixture supplied to the processing chamber undergoes heat treatment while swirling in the processing chamber, and then cools.
[0064] The hot air for heat treatment of the mixture is supplied by the hot air supply unit 7 and distributed by the distribution member 12. The hot air is spirally swirled in the processing chamber by a vortex member 13 for swirling the hot air, and is introduced from the outlet 11 of the hot air supply unit. The vortex member 13 is configured to have a plurality of blades to control the vortex of the hot air according to the number of blades and their angles. In order to supply the hot air to the processing chamber, the temperature of the hot air at the outlet of the hot air supply unit 7 is preferably 100 to 300°C, more preferably 130 to 170°C. If the temperature of the hot air at the outlet of the hot air supply unit is within this range, the fusion or adhesion of the colorant particles caused by excessive heating of the mixture can be prevented, and the colorant particles can be uniformly spheroidized. The average circularity at this time is preferably 0.955 to 0.980.
[0065] In addition, the heat-treated white toner particles are cooled with cold air supplied by the cold air supply unit 8. The temperature of the cold air supplied by the cold air supply unit 8 is preferably -20 to 30°C. If the temperature of the cold air is within this range, the heat-treated toner particles can be effectively cooled, and fusion or adhesion of the heat-treated toner particles can be prevented without impairing uniform spheroidization of the mixture. The absolute moisture content of the cold air is preferably 0.5 to 15.0 g / m 3 .
[0066] Next, the cooled heat-treated white toner particles are recovered by a recovery unit 10 provided at the lower end of the process chamber. Note that a fan (not shown) is provided upstream of the recovery unit and is configured to attract and convey the white toner particles.
[0067] The powder particle supply port 14 is arranged so that the vortex direction of the supplied mixture and the vortex direction of the hot air are in the same direction. The recovery unit 10 of the surface treatment device is arranged at the periphery of the treatment chamber to maintain the vortex direction of the vortex powder particles. In addition, the device is configured so that the cold air supplied by the cold air supply unit 8 is supplied along the tangential direction from the periphery of the device to the inner peripheral surface of the treatment chamber. The vortex direction of the white toner particles before the heat treatment supplied by the powder supply port, the vortex direction of the cold air supplied by the cold air supply unit, and the vortex direction of the hot air supplied by the hot air supply unit are all in the same direction. For this reason, the vortex flow inside the device is enhanced without causing any turbulence in the treatment chamber, and a strong centrifugal force is applied to the white toner particles before the heat treatment to further improve the dispersibility of the white toner particles before the heat treatment, thereby resulting in heat-treated toner particles with a uniform shape and few adhered particles.
[0068] In the next step, the obtained toner particles are subjected to external addition treatment as necessary.
[0069] Examples of the mixing apparatus used for the external addition treatment include a double cone mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a mechanical hybridizer (manufactured by NIPPON COKE & ENGINEERING CO., LTD.).
[0070] Next, the measurement methods of physical properties related to the present invention will be described.
[0071] <Method for measuring work function of white pigment and inorganic fine particles>
[0072] The work function is measured using a surface analyzer (AC-2, low energy electron counting method, manufactured by RIKEN KEIKI Co., Ltd.). In the present invention, a deuterium lamp is used in the device, and the setting value of the light irradiation amount is 500nW. Monochromatic light is selected with a spectroscope. The size of the spot is 4mm square. The range of the energy scan is set to 4.20 to 6.20eV, and the interval is set to 0.05eV. The sample is irradiated with a measurement time of 10 seconds / 1 point to detect photoelectrons released from the sample surface. The work function is measured with a repetition accuracy (standard deviation) of 0.02eV. The unit for powder measurement is used to measure the powder.
[0073] Figure 2 Schematic diagram of a unit for measuring powder. (a) is a plan view of the unit 20, (b) is a side view of a part of the unit 20, and (c) is a perspective view. The unit 20 has a recess 20a with a diameter of 15 mm and a depth of 3 mm for accommodating samples in the center of a stainless steel disc with a diameter of 30 mm and a height of 5 mm. The sample is placed in the recess 20a without pressing the sample downward using a measuring spoon, and then the surface of the sample is leveled using the edge of a knife. In this state, the measuring unit is fixed to a predetermined position of the sample stage for measurement.
[0074] like Figure 3 As shown, the measuring unit (a) is fixed to a predetermined position of the sample stage 21 so that the irradiation surface of the sample is flat relative to the irradiation direction of the measuring light L. As a result, the released photoelectrons 22 are more effectively detected by the detector (photomultiplier tube) 23. In this surface analysis, the release of photons starts from a certain energy value (eV) by scanning the excitation energy of monochromatic light from low energy to high energy. This energy value is called the work function (eV). In order to ensure the reproducibility of the data, the measurement sample is a product placed under the conditions of temperature 23°C / humidity 60RH% for 24 hours.
[0075] <Method for measuring the contents of white pigment and inorganic fine particles in white toner particles>
[0076] 2 (ml) of a nonionic surfactant (preferably CONTAMINON N (manufactured by Wako Pure Chemical Industries, Ltd.: trade name)) is added to 200 (ml) of deionized water and dispersed with an ultrasonic disperser for 10 hours to float the total amount of external additives added to the white toner. The content of the white pigment or inorganic fine particles present in the white toner particles is calculated by fluorescent X-ray measurement.
[0077] The fluorescent X-ray measurement of the elements was performed in accordance with JIS K 0119-1969, and specifically is as follows.
[0078] A wavelength dispersive X-ray fluorescence analyzer "Axios" (manufactured by PANalytical Ltd.) was used as a measuring device, and attached dedicated software "SuperQver.4.0F" (manufactured by PANalytical Ltd.) for setting measurement conditions and analyzing data obtained by the measurement was used. Note that Rh was used as the anode of the X-ray tube, the measurement atmosphere was vacuum, the diameter of the measurement (the diameter of the collimator mask) was 27 mm, and the measurement time was 10 seconds. Detection was performed with a proportional counter (PC) in the measurement of light elements, and with a scintillation counter (SC) in the measurement of heavy elements.
[0079] The pellets prepared as follows were used as the measurement sample: about 4 g of the toner was placed in a dedicated aluminum ring for pressing and flattened. The toner was pressed at 20 MPa for 60 seconds using a tablet forming press "BRE-32" (manufactured by Maekawa Testing Machine Mfg. Co., LTD.) to form pellets having a thickness of about 2 mm and a diameter of about 39 mm.
[0080] The measurement was performed under the above conditions, and the element was identified based on the obtained X-ray peak position. The concentration was calculated from the count rate (unit: cps) of the number of X-ray photons per unit time.
[0081] In the case of white pigment, add white pigment in an amount of 10.0 mass parts relative to 100 mass parts of binder resin, then use coffee grinder to fully mix. The resulting mixture is used as a calibration curve sample. Similarly, white pigment is mixed with binder resin in an amount of 30.0 mass parts, 50.0 mass parts and 70.0 mass parts respectively. These mixtures are used as calibration curve samples.
[0082] In the case of inorganic fine particles, the inorganic fine particles were mixed in amounts of 0.1 parts by mass, 1.0 parts by mass, and 2.5 parts by mass, respectively, relative to 100 parts by mass of the binder resin. These mixtures were used as samples for calibration curves.
[0083] As described above, these samples were prepared into pellets of samples for calibration curves using a tablet forming press to measure the count rate (unit: cps) of Si-Kα rays observed at a diffraction angle (2θ) of 109.08°, wherein PET was used as an analytical crystal. At this time, the accelerating voltage and current values of the X-ray generator were 24 kV and 100 mA, respectively. The count rate of the resulting X-rays was plotted as the ordinate and the calibration curve was plotted as the abscissa with the amount of white pigment or inorganic fine particles added in each sample to create a calibration curve derived from a linear function.
[0084] Next, the toner to be analyzed is formed into pellets using a tablet forming press as described above to measure the count rate of Si-Kα rays thereof. From the above calibration curve, the content of the white pigment or inorganic fine particles in the toner is calculated.
[0085] <Method for measuring softening point (Tm) of binder resin>
[0086] The softening point of the resin was measured using a constant load extrusion capillary rheometer "Rheological Properties Evaluator Flowtester CFT-500D" (manufactured by SHIMADZU Corporation) according to the manual attached to the device. In this device, the sample for measurement filled in the cylinder is melted by heating while a constant load is applied from the upper part of the sample for measurement by a piston. The molten sample for measurement is extruded from the die head at the bottom of the cylinder. Thus, a flow curve showing the relationship between the piston stroke amount and the temperature at this time can be obtained.
[0087] In the present invention, the "melting temperature according to the 1 / 2 method" described in the manual attached to the "Rheological Properties Evaluator Flowtester CFT-500D" is defined as the softening point. The melting temperature according to the 1 / 2 method is calculated as follows. First, 1 / 2 of the difference between the piston stroke amount Smax at the end of outflow and the piston stroke amount Smin at the start of outflow is determined (which is defined as X, X = (Smax-Smin / 2). The temperature of the flow curve when the piston stroke amount in the flow curve reaches X corresponds to the melting temperature according to the 1 / 2 method.
[0088] A cylindrical sample for measurement having a diameter of about 8 mm is prepared by compression molding about 1.0 g of the resin at about 10 MPa for about 60 seconds at 25° C. using a tablet molding press (eg, NT-100H, manufactured by NPa SYSTEM CO., LTD.).
[0089] The CFT-500D was set to the following measurement conditions.
[0090] Test mode: Heating method
[0091] Starting temperature: 50℃
[0092] Reach temperature: 200℃
[0093] Measuring interval: 1.0℃
[0094] Heating rate: 4.0℃ / min
[0095] Piston cross-sectional area: 1.000cm 2
[0096] Test load (piston load): 10.0kgf (0.9807MPa)
[0097] Warm-up time: 300 seconds
[0098] Die hole diameter: 1.0mm
[0099] Mold length: 1.0mm
[0100] <Measurement of Weight Average Molecular Weight of Binder Resin>
[0101] The molecular weight distribution of THF-soluble matter in the binder resin is measured by gel permeation chromatography (GPC) as follows.
[0102] The column is stabilized in a heating chamber at 40°C, and tetrahydrofuran (THF) as a solvent is flowed into the column at a flow rate of 1 ml / min at this temperature. About 100 μl of the THF sample solution is injected for measurement. In the measurement of the molecular weight of the sample, the molecular weight distribution possessed by the sample is calculated from the relationship between the count value and the logarithmic value of the calibration curve created by several monodisperse polystyrene standard samples. As the standard polystyrene sample for creating the calibration curve, for example, a polystyrene sample having a molecular weight of about 10 manufactured by Tosoh Corporation or Showa Denko KK is used. 2 Up to 10 7Those of. Appropriately, at least 10 kinds of standard polystyrene samples or the like are used. A refractive index (RI) detector is used as a detector. As the column, it is preferred to combine several commercially available polystyrene gel columns. Examples thereof include the following combinations: Shodex GPCKF-801, 802, 803, 804, 805, 806, 807 and 800P manufactured by Showa Denko KK, and TSKgel G1000H (H XL )、G2000H(H XL )、G3000H(H XL )、G4000H(H XL )、G5000H(H XL )、G6000H(H XL )、G7000H(H XL ) and TSKgurd columns.
[0103] The samples were prepared as follows.
[0104] 50 mg of the sample was placed in 10 ml of THF and placed at 25 ° C for several hours. The sample was then shaken sufficiently to mix the sample well with THF (until the aggregates of the sample disappeared), and further placed for more than 12 hours. It was controlled so that the sample was placed in THF for a total of 24 hours. Subsequently, the product was used as a GPC sample by a sample treatment filter (pore size: 0.2 μm or more and 0.5 μm or less, for example, MAISHORI DISK H-25-2 (manufactured by Tosoh Corporation)).
[0105] <Measurement of Melting Point of Wax>
[0106] The melting point of the wax is defined as the peak temperature of the maximum endothermic peak in a DSC curve obtained when measured using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments) in accordance with ASTM D3418-82.
[0107] The temperature of the detector of the equipment is corrected using the melting points of zinc and indium, while the heat of fusion of indium is used to correct the heat. Specifically, about 2 mg of the sample is accurately weighed and placed in an aluminum pan, and an empty aluminum pan is used as a reference. The measurement is performed at a temperature rise rate of 10°C / min at a measurement temperature between 30 and 200°C. During the measurement, the temperature is once raised to 200°C, reduced to 30°C, and heated again. The temperature of the maximum endothermic peak of the DSC curve in the temperature range of 30 to 200°C during the secondary heating process is defined as the melting point.
[0108] <Measurement of Weight Average Particle Diameter (D4) of Toner>
[0109] The weight average particle size (D4) of the toner is determined as follows: the particle size is measured with 25000 channels (effective measurement channel number) using a precision particle size distribution measuring device "Coulter counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.) including a 100 μm orifice tube and utilizing a micropore resistance method and attached dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) for setting measurement conditions and analyzing data obtained by measurement. The data obtained by measurement are analyzed, and then the weight average particle size (D4) of the toner is calculated. The electrolyte aqueous solution used for measurement may be special grade sodium chloride such as "ISOTON II" (manufactured by Beckman Coulter, Inc.) dissolved in deionized water and controlled to a concentration of about 1% by mass.
[0110] Before performing measurement and analysis, the dedicated software was set as follows.
[0111] On the "Screen for Changing the Standard Measurement Method (SOM)" of the dedicated software, set the total count of the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using the "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.). The threshold and noise level are automatically set by pressing the "Threshold / Noise Level Measurement" button. Set the current to 1600 μA, the gain to 2, and the electrolyte solution to ISOTON II. Check "Post-Measurement Mouth Tube Flush". On the "Screen for Pulse to Particle Size Conversion Settings" of the dedicated software, set the element interval to logarithmic particle size, the particle size element to 256 particle size elements, and the particle size range to 2 μm to 60 μm.
[0112] The specific measurement method includes the following steps (1) to (7).
[0113] (1) Place approximately 200 ml of electrolyte aqueous solution into a 250 ml glass round-bottom beaker for Multisizer 3. Place the beaker on the sample stage and stir with a stirring rod in a counterclockwise direction at a speed of 24 rpm. Remove dirt and bubbles in the orifice tube using the "pore flushing" function of the analysis software.
[0114] (2) About 30 ml of an aqueous electrolyte solution was placed in a 100 ml glass flat-bottom beaker. About 0.3 ml of a dilution prepared by diluting "CONTAMINON N" (a 10 mass % aqueous solution of a neutral detergent (pH: 7) for washing precision measuring equipment, which consists of a nonionic surfactant, an anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) by 3 times the mass with deionized water was added thereto as a dispersant.
[0115] (3) A predetermined amount of deionized water was placed in a water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki-Bios Co., Ltd.) having a power output of 120 W in which two vibrators of an oscillation frequency of 50 kHz were built with a phase shift of 180°. To the water tank, about 2 mL of CONTAMINON N was added.
[0116] (4) The beaker of (2) above is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. The height position of the beaker is adjusted so that the resonance state of the liquid surface of the aqueous electrolyte solution in the beaker is maximized.
[0117] (5) While ultrasonic waves are applied to the aqueous electrolyte solution in the beaker of (4), about 10 mg of the toner is added little by little to the aqueous electrolyte solution and dispersed therein. The ultrasonic dispersion treatment is continued for 60 seconds. During the ultrasonic dispersion, the temperature of the water in the water tank is appropriately adjusted to 10° C. to 40° C.
[0118] (6) The electrolyte aqueous solution of (5) above in which the toner is dispersed is dropped into the round-bottom beaker of (1) above set in the sample stage using a pipette. The measurement concentration is adjusted to about 5%. Then, measurement is performed until the number of measured particles reaches 50,000.
[0119] (7) The measurement data is analyzed by the dedicated software attached to the equipment, and the weight average particle size (D4) is calculated. When the graph / volume % is set by the dedicated software, the weight average particle size (D4) is the "average diameter" on the analysis / volume statistics (arithmetic mean) interface.
[0120] <Method for measuring average circularity of toner>
[0121] The average circularity of the toner is measured using a flow-type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) under the conditions of measurement and analysis at the time of calibration.
[0122] The principle of measurement by the flow-type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) is to capture the image of the flowing particles as a still image and perform image analysis on it. The sample added to the sample chamber is supplied to the flat sheath flow cell by the sample suction syringe. The sample supplied to the flat sheath flow cell is clamped by the sheath liquid to form a flat flow. The sample passing through the inside of the flat sheath flow cell is irradiated with a stroboscopic light at intervals of 1 / 60 seconds. Thus, the image of the flowing particles can be captured as a still image. This is a flat flow and can be captured in focus. The image of the particles is captured with a CCD camera. Each captured image is image processed with an image processing resolution of 512×512 pixels (0.37μm×0.37μm per pixel), and then the contour of each particle image is extracted, and the projected area S and perimeter L of the particle image are measured.
[0123] Next, the circle equivalent diameter and circularity are determined using the area S and the circumference L. The circle equivalent diameter represents the diameter of a circle having the same area as the projected area of the particle image, and the circularity C is defined as the value obtained by dividing the circumference of the circle determined by the circle equivalent diameter by the circumference of the projected image of the particle. The circularity C is calculated by the following equation.
[0124] Circularity C = 2 × (π × S) 1 / 2 / L
[0125] The circularity of a particle image having a circular shape is 1.000. As the particle image has greater concavity and convexity on its circumference, the value of the circularity is smaller. The circularity of the particles is calculated, and the range of the circularity of 0.200 to 1.000 is divided into 800 parts. The arithmetic mean of the obtained circularity is calculated, and this value is defined as the average circularity.
[0126] The specific measuring method is described as follows. First, about 20mL of ion exchange water from which solid impurities have been removed in advance is placed in a glass container. Add about 0.2ml of a diluent of a dispersant "CONTAMINON N" (a 10% aqueous solution of a neutral detergent (pH: 7) for washing precision measuring equipment, which is composed of a nonionic surfactant, anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) to the ion exchange water. The diluent is prepared by diluting "CONTAMINON N" with about 3 times the mass of ion exchange water. Further add about 0.02g of the measurement sample, and use an ultrasonic disperser to disperse for 2 minutes to prepare a dispersion for measurement. At this time, the dispersion is appropriately cooled to a temperature above 10°C and below 40°C. The ultrasonic disperser used was a table-top ultrasonic cleaning disperser ("VS-150" (manufactured by VELVO-CLEAR KK) having an oscillation frequency of 50 kHz and an electrical output of 150 W. A predetermined amount of ion exchange water was put into a water tank, and about 2 mL of CONTAMINON N was added to the water tank.
[0127] During the measurement, a flow-type particle image analyzer equipped with a standard objective lens (magnification: 10×) was used. A particle sheath "PSE-900A" (manufactured by Sysmex Corporation) was used as a sheath liquid. The dispersion prepared according to the process was introduced into the flow-type particle image analyzer, and 3000 toner particles were measured in the HPF measurement mode and the total count mode. The binarization threshold during particle analysis was 85%, and the analyzed particle size was indicated. Thus, the number ratio (%) and the average circularity of the particles within the range were calculated. In the case where the average circularity of the toner is a circle equivalent diameter of 1.98 μm or more and 39.96 μm or less, the average circularity of the toner was obtained.
[0128] In the measurement, the focus is automatically adjusted before the start of measurement using standard latex particles (eg, "RESEARCH AND TEST PARTICLES Latex Microsphere Suspensions 5200A" manufactured by Duke Scientific Co., diluted with ion exchange water). Subsequently, the focus is preferably adjusted every 2 hours from the start of measurement.
[0129] In the examples of the present application, measurements were performed on the conditions of measurement and analysis set when the calibration certificate was received, except that the analyzed particle diameter was limited to a circle-equivalent diameter of 1.98 μm or more and less than 39.69 μm.
[0130] [Example]
[0131] The basic constitution and features of the present invention have been described above. The present invention will now be specifically described based on embodiments. However, these embodiments should not be construed as limiting the present invention.
[0132] <Production Example of Inorganic Fine Particles 1>
[0133] The combustion furnace used is a hydrocarbon-oxygen mixed burner with a double-tube structure capable of forming an inner flame and an outer flame. A dual-fluid nozzle for spraying slurry is arranged at the center of the burner, and a silicon compound (hexamethylcyclotrisiloxane) as a raw material is introduced. Hydrocarbon-oxygen combustible gas is ejected from around the dual-fluid nozzle to form an inner flame and an outer flame as a reducing atmosphere. The atmosphere, temperature and length of the flame are regulated by controlling the amount of combustible gas and oxygen and its flow rate. The silicon compound forms fine silica particles in the flame, and the fine silica particles are further fused into a desired particle size. After cooling, the obtained fine particles are collected with a bag filter, etc., thereby obtaining inorganic fine particles 1 as fine silica particles with a number average diameter of 120nm.
[0134] <Production Example of Inorganic Fine Particles 2>
[0135] While stirring the sodium stearate aqueous solution with a homomixer, a zinc sulfate aqueous solution was added to prepare a fine zinc stearate slurry. The slurry was filtered. The obtained metal soap filter cake was washed twice with water and then washed with methanol. The washed obtained metal soap filter cake was vacuum dried and repeatedly crushed with a jet mill to obtain inorganic fine particles 2 as zinc stearate fine particles with a number average diameter of 250 nm.
[0136] <Production Example of Inorganic Fine Particles 3>
[0137] Ilmenite ore containing 50 mass % TiO2 equivalent was dried at 150°C for 3 hours, and sulfuric acid was added to dissolve the ilmenite, thereby obtaining an aqueous solution of TiOSO4.
[0138] After concentrating the obtained aqueous solution, 10 parts by mass of a titanium dioxide sol having anatase crystals was added as a seed, followed by hydrolysis at 170° C. A slurry of TiO(OH) 2 containing impurities was prepared.
[0139] The slurry was repeatedly washed at a pH of 5 to 6 to sufficiently remove sulfuric acid, FeSO4 and impurities. Thus, a slurry of high-purity metatitanic acid [TiO(OH)2] was prepared.
[0140] After filtering the slurry, 0.5 parts by mass of potassium dihydrogen phosphate (KH2PO4) was added, followed by firing at 240° C. for 4 hours. Then, the product was repeatedly subjected to a crushing treatment using a jet mill, thereby obtaining titanium oxide fine particles having anatase crystals.
[0141] The obtained titanium oxide fine particles were dispersed in ethanol. While the titanium oxide fine particles were stirred, 5 parts by mass of isobutyltrimethoxysilane as a surface treatment agent was dropped into 100 parts by mass of the titanium oxide fine particles to perform a reaction.
[0142] After drying, the reactant was subjected to heat treatment at 170° C. for 3 hours, and crushing treatment was repeated with a jet mill until titanium dioxide aggregates disappeared. Thus, inorganic fine particles 3 were obtained as titanium oxide fine particles having a number average diameter of 40 nm.
[0143] <Production Example 1 of White Pigment>
[0144] Ilmenite ore containing 50 mass % TiO2 equivalent was dried at 150°C for 3 hours, and sulfuric acid was added to dissolve the ilmenite to prepare an aqueous solution of TiOSO4.
[0145] After concentrating the obtained aqueous solution, 8 parts by mass of a titanium dioxide sol having rutile crystals was added as a seed, followed by hydrolysis at 150° C. A slurry of TiO(OH) 2 containing impurities was prepared.
[0146] The slurry was repeatedly washed at a pH of 5 to 6 to sufficiently remove sulfuric acid, FeSO4 and impurities. Thus, a slurry of high-purity metatitanic acid [TiO(OH)2] was prepared.
[0147] After filtering the slurry, 0.5 parts by mass of lithium carbonate (Li2CO3) was added, followed by firing at 300°C for 4 hours. Then, the product was repeatedly crushed with a jet mill to obtain white pigment 1 as titanium oxide fine particles having rutile crystals and a number average diameter of 55 nm.
[0148] <Production Example 2 of White Pigment>
[0149] An alcohol aqueous solution of 15.0 parts by mass of water and 165.7 parts by mass of isopropyl alcohol was added to a mixed solution of 100.0 parts by mass of aluminum isopropylate and 11.1 parts by mass of isopropyl alcohol to perform hydrolysis (molar ratio of water / aluminum alkoxide = 1.7, water content in the alcohol aqueous solution: 8.3 mass%).
[0150] In the next step, 99.3 parts by mass of isopropanol was separated by distillation for recovery, and then, 24.9 parts by mass of water and 64.2 parts by mass of an alcohol aqueous solution of isopropanol were further added for hydrolysis (water / aluminum alkoxide molar ratio = 2.8). After the hydrolysis step was completed, the water content in the slurry was 7.8% by mass.
[0151] Water and isopropyl alcohol were removed from the resulting suspension containing aluminum hydroxide, water, and isopropyl alcohol, thereby obtaining White Pigment 2 as aluminum hydroxide fine particles having a number average particle diameter of 60 nm.
[0152] <Production Example 3 of White Pigment>
[0153] 200ml ethanol / water mixed solution (ethanol content: 50%) is cooled to -20 to 10 ℃, and 160g Ca (OH) 2 is added thereto. While the obtained slurry-like liquid is vigorously stirred, a mixed gas of carbon dioxide / nitrogen (the content of carbon dioxide: 30%) is introduced from the bottom of the container at a flow rate of 500 to 5000ml / min to react until pH begins to decrease. At this point, the introduction rate of the reaction temperature and carbon dioxide is adjusted to prepare a slurry comprising a synthetic calcium carbonate having an average primary particle diameter of 130nm. In addition, while maintaining a low temperature state, each dispersion is filtered, then fully washed with pure water, and then dried to obtain synthetic calcium carbonate.
[0154] Water adjusted to 70°C is added to the obtained synthetic calcium carbonate so that the solid content is 10% by mass, and the obtained synthetic calcium carbonate is formed into slurry using a stirring dispersion machine. While using a dispersion machine to stir the slurry of 1kg synthetic calcium carbonate, 0.2 to 4g of saponified stearic acid is added, followed by stirring for 1 to 30 minutes, and then, dehydration is pressed. The dehydrated cake is dried, and then, powdered. Subsequently, the fine particle component is removed with an air classifier, thereby obtaining the white pigment 3 as a calcium carbonate particle with a number average diameter of 90nm.
[0155] <Production Example 4 of White Pigment>
[0156] Aluminum hydroxide having a purity of 99.0% was used as a raw material. A production method by the Bayer process was used, and the firing temperature conditions and atmosphere were appropriately adjusted to synthesize aluminum oxide fine particles having a number average particle diameter of 110 (nm).
[0157] White pigment 4 was obtained as aluminum oxide fine particles having a number average particle diameter of 80 (nm).
[0158] <Production Example 5 of White Pigment>
[0159] 600g of fine zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd., median particle size (D50): 0.2μm) was re-pulped in water and mixed with 3.50% by mass of a dispersant (manufactured by Kao Corporation, Poise 532A) relative to the mass of the fine zinc oxide. 0.61% by mass of acetic acid was mixed to prepare a slurry with a concentration of 600g / l. Next, the slurry was spray-dried with a laboratory spray dryer model DCR (manufactured by Sakamoto Giken KK) to obtain granulated particles. The product was placed in a refractory box and fired at 1150°C for 4 hours while standing. The product was cooled and then dispersed in 1.0L of water. The resulting slurry was filtered and dried to obtain white pigment 5 as fine zinc oxide particles with a number average diameter of 30μm.
[0160] <Production Example 6 of White Pigment>
[0161] At 40°C, 0.80 equivalents of an alkaline substance and 1 equivalent of a water-soluble magnesium salt that had been previously refined were mixed to react. Subsequently, the reaction product with the reaction mother solution was heated under a pressure of about 5.9 MPa for about 4 hours to obtain magnesium hydroxide. The obtained magnesium hydroxide was fired at 1450°C for 3 hours using a chopping alloy furnace. The obtained calcined product was crushed (fragmented) and classified to obtain white pigment 6 as magnesium oxide particles with a number average diameter of 60 nm.
[0162] <Production Example 7 of White Pigment>
[0163] A 50 g / liter (concentration as ZrO2) aqueous solution of zirconium oxychloride was hydrolyzed to a hydrolysis rate of 90% by boiling under reflux.
[0164] The average primary particle size of the obtained hydrated zirconium oxide sol was 100 nm.
[0165] A 1 mol / L sodium hydroxide aqueous solution was added to the hydrolyzed solution to adjust the pH to 12. While stirring the pH-adjusted aqueous solution, the aqueous solution was kept under reflux at a boiling temperature for 24 hours. Subsequently, the aqueous solution was filtered and washed with 80° C. pure water until the pH of the filtrate reached 8. A slurry of 200 g / liter (concentration in terms of ZrO2) was prepared.
[0166] The slurry was spray dried with a spray dryer and then calcined by holding at 900° C. for 2 hours. Thus, white pigment 7 was obtained as zirconium oxide fine particles having a number average particle diameter of 60 nm.
[0167] <Production Example 8 of White Pigment>
[0168] Fine silica particles are prepared by a combustion method, wherein hexamethylcyclotrisiloxane is used as a raw material. The combustion furnace used is a hydrocarbon-oxygen mixed burner with a double-tube structure capable of forming an inner flame and an outer flame. A dual-fluid nozzle for spraying slurry is arranged at the center of the burner, and a silicon compound as a raw material is introduced. Hydrocarbon-oxygen combustible gas is ejected from around the dual-fluid nozzle to form an inner flame and an outer flame as a reducing atmosphere. The atmosphere, temperature and length of the flame are regulated by controlling the amount of combustible gas and oxygen and its flow rate. The silicon compound forms fine silica particles in the flame, and the fine silica particles are further fused into a desired particle size. After cooling, the resulting fine particles are collected with a bag filter, etc., thereby obtaining white pigment 8 as fine silica particles with a number average diameter of 100nm.
[0169] [Production Example of Polyester L]
[0170] Polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane: 72.0 parts by mass (0.20 mol; relative to the total molar amount of the polyol: 100.0 mol%)
[0171] Terephthalic acid: 28.0 parts by mass (0.17 mol; 96.0 mol% relative to the total molar amount of the polycarboxylic acid)
[0172] ·2-Ethylhexanoate tin (esterification catalyst): 0.5 parts by mass
[0173] The above materials were weighed and placed in a reaction tank equipped with a cooling tube, a stirrer, a nitrogen inlet tube and a thermocouple. Next, the flask was purged with nitrogen and gradually heated under stirring. The materials were reacted for 4 hours while stirring at a temperature of 200°C.
[0174] Furthermore, the internal pressure of the reaction tank was reduced to 8.3 kPa and maintained for 1 hour. Then, the reaction tank was cooled to 180° C. and the internal pressure was returned to atmospheric pressure (first reaction step).
[0175] Trimellitic anhydride: 1.3 parts by mass (0.01 mol; 4.0 mol% relative to the total molar amount of the polycarboxylic acid)
[0176] Tert-butylcatechol (polymerization inhibitor): 0.1 parts by mass
[0177] Subsequently, the above materials were added. The internal pressure of the reaction tank was reduced to 8.3 kPa. While maintaining the temperature at 180° C., the reaction was performed for 1 hour. After confirming that the softening point measured according to ASTM D36-86 reached 94° C., the temperature was lowered to terminate the reaction (second reaction step), thereby obtaining polyester L. The softening point (Tm) of the obtained polyester L was 94° C. and the glass transition temperature (Tg) was 57° C.
[0178] [Production Example of Polyester H]
[0179] Polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane: 72.3 parts by mass (0.20 mol; relative to the total molar amount of the polyol: 100.0 mol%)
[0180] Terephthalic acid: 18.3 parts by mass (0.11 mol; 65.0 mol% relative to the total molar amount of the polycarboxylic acid)
[0181] Fumaric acid: 2.9 parts by mass (0.03 mol; 15.0 mol% relative to the total molar amount of the polycarboxylic acid)
[0182] ·2-Ethylhexanoate tin (esterification catalyst): 0.5 parts by mass
[0183] The above materials were weighed and placed in a reaction tank equipped with a cooling tube, a stirrer, a nitrogen inlet tube and a thermocouple. Next, the flask was purged with nitrogen and then gradually heated under stirring. The materials were reacted for 2 hours while stirring at a temperature of 200°C.
[0184] Furthermore, the internal pressure of the reaction tank was reduced to 8.3 kPa and maintained for 1 hour. The reaction tank was cooled to 180° C. and the internal pressure was returned to atmospheric pressure (first reaction step).
[0185] Trimellitic anhydride: 6.5 parts by mass (0.03 mol; 20.0 mol% relative to the total molar amount of the polycarboxylic acid)
[0186] Tert-butylcatechol (polymerization inhibitor): 0.1 parts by mass
[0187] Subsequently, the above materials were added. The internal pressure of the reaction tank was reduced to 8.3 kPa. While maintaining the temperature at 160° C., the reaction was performed for 15 hours. After confirming that the softening point measured according to ASTM D36-86 reached 132° C., the temperature was lowered to terminate the reaction (second reaction step), thereby obtaining polyester H. The softening point (Tm) of the obtained polyester H was 132° C. and the glass transition temperature (Tg) was 61° C.
[0188] <Production Example of Toner 1>
[0189]
[0190] The raw materials listed in the above formula were mixed by a Henschel mixer (FM-75, manufactured by Mitsui Mining Co., Ltd.) for 20 s. -1The mixture was mixed with a rotation time of 5 min at a rotation number of 1000 rpm. Subsequently, the resulting mixture was kneaded with a twin-screw kneader (PCM-30 type, manufactured by Ikegai Corp.) set to a temperature of 125° C. The resulting kneaded product was cooled and coarsely pulverized to less than 1 mm with a hammer mill to obtain a coarsely pulverized product. The coarsely pulverized product was finely pulverized with a mechanical pulverizer (T-250, manufactured by FREUND-TURBO CORPORATION). In addition, the pulverized product was classified using a rotary classifier (200TSP, manufactured by Hosokawa Micron Corporation) to obtain toner particles. For the operating conditions of the rotary classifier (200TSP, manufactured by Hosokawa Micron Corporation), the number of revolutions of the classifying rotor was set to 50.0s -1 The weight average particle size (D4) of the obtained toner particles was 5.7 μm.
[0191] 4.5 parts by mass of the inorganic fine particles 1 are added to 100 parts by mass of the obtained toner particles, followed by mixing with a Henschel mixer (FM-75 type, manufactured by Mitsui Mining Co., Ltd.) for 30 seconds. -1 Mix with a rotation time of 10 minutes. Figure 1 The surface treatment apparatus shown in the figure subjected the obtained mixture to heat treatment, thereby obtaining heat-treated toner particles. As for the operating conditions, the supply amount was 5 kg / hr, the hot air temperature C was 220°C, and the hot air flow speed was 6 m / s. 3 / minute, the cold air temperature E is 5℃, and the cold air flow speed is 4m 3 / minute, the absolute moisture content of cold air is 3g / m 3 , the fan air volume is 20m 3 / min, and the injection wind flow velocity is 1m 3 The obtained treated toner particles had an average circularity of 0.963 and a weight average particle size (D4) of 6.2 μm.
[0192] 0.5 parts by mass of titanium dioxide fine particles containing primary particles having a number average particle diameter of 32.0 nm were added to 100 parts by mass of the resulting treated toner particles, followed by mixing at a peripheral speed of 45 m / sec for 5 minutes using a Henschel mixer (FM75 type, manufactured by Mitsui Miike Kakoki K.K.). The product was passed through an ultrasonic vibration sieve having an opening of 54 μm, thereby obtaining Toner 1.
[0193] <Production Examples of Toners 2 to 18 and Comparative Toners 1 to 4>
[0194] Toners 2 to 18 and Comparative Toners 1 to 4 were prepared in the same manner as in Production Example of Toner 1, except that White Pigments 2 to 8 as shown in Table 1 were used instead of White Pigment 1 or Inorganic Fine Particles 2 or Inorganic Fine Particles 3 were used instead of Inorganic Fine Particles 1.
[0195] <Production Example of Two-Component Developer 1>
[0196] Toner 1 and magnetic ferrite carrier particles (number average particle size: 35 μm) whose surfaces are covered with a silicone resin were charged into a V-type mixer (V-10 type: manufactured by Tokuju Seisakusho KK) so that the toner concentration was 9% by mass. -1 These were mixed under the conditions of 0.1% to 0.5% and a rotation time of 5 minutes to obtain a two-component developer 1.
[0197] <Production Examples of Two-Component Developers 2 to 18 and Comparative Two-Component Developers 1 to 4>
[0198] Two-component developers 2 to 18 and comparative two-component developers 1 to 4 were prepared in the same manner as in Production Example of Two-Component Developer 1, except that Toner 1 was replaced with Toners 2 to 18 and Comparative Toners 1 to 4 as shown in Table 1.
[0199] [Example 1]
[0200] The two-component developer 1 was evaluated as follows. The evaluation results are shown in Table 2.
[0201] <Evaluation 1>
[0202] The two-component developer 1 was loaded into the cyan station of a full-color copier imagePRESS C800 manufactured by Canon Inc., and the developing conditions were appropriately adjusted so that the amount of toner applied to the paper to form a FFH image (solid image) was 1.2 mg / cm 2 .
[0203] Black paper having an image density of 1.5 or more was used as the paper for evaluation. Evaluations 1-1 to 1-3 were performed while replenishing Toner 1 as needed. The image density was measured using an X-Rite color reflection densitometer (500 series: manufactured by X-Rite, Incorporated).
[0204] The FFH image represents an image corresponding to the 256th gray level (solid portion), where the 256th gray level is represented by hexadecimal.
[0205] [Evaluation 1-1]
[0206] A 500-sheet continuous paper passing test (A4 horizontal orientation, printing ratio: 80%) was conducted in a low temperature and low humidity environment (15°C, 10% RH). During the 500-sheet continuous paper passing test, the paper was passed under the same developing conditions and transfer conditions (uncalibrated) as on the first sheet.
[0207] The image density of all FFH image portions (solid portions) of the images formed on 500 sheets was measured, and the difference between the highest density and the lowest density was calculated. The evaluation criteria are as follows:
[0208] A: Less than 0.05 (very excellent)
[0209] B: 0.05 or more and less than 0.10 (good)
[0210] C: 0.10 or more and less than 0.20 (level without problems in the present invention)
[0211] D: 0.20 or more (unacceptable in the present invention)
[0212] [Evaluation 1-2]
[0213] The image output environment was changed from a low temperature and low humidity environment (15°C, 10% RH) to a high temperature and high humidity environment (30°C, 80% RH) over 8 hours. Immediately thereafter, a 500-sheet continuous paper feed test (A4 horizontal, print ratio: 80%) was performed, and the stability of the image density was evaluated in the same manner as above.
[0214] [Evaluation 1-3]
[0215] The full-color copier was placed in a high temperature and high humidity environment (30°C, 80% RH) for more than 10 hours to fully stand in the use environment. A 500-sheet continuous paper feed test (A4 horizontal, print ratio: 80%) was performed in the same manner as above, and the stability of the image density was evaluated in the same manner as above.
[0216] <Evaluation 2>
[0217] A remodeled machine of imageRUNNER ADVANCE C5255, a full-color copying machine manufactured by Canon Inc., was used as an image forming apparatus, and the two-component developer 1 was loaded into the developing unit of the magenta station to perform the following evaluation.
[0218] The evaluation was conducted under normal temperature and humidity environment (23°C, 50% RH), and the evaluation paper was ordinary copy paper GFC-081 (A4, basis weight: 81.4 g / m 2 , commercially available from Canon Marketing Japan Inc.).
[0219] An image was formed while changing the amount of toner applied to the paper. The relationship between the image density and the amount of toner applied to the paper was examined. From the obtained relationship, the amount of toner applied where the image density was 0.40 was found. From the amount of toner applied (mg / cm 2 ), the tinting strength of the toner was evaluated according to the following criteria:
[0220] A: Less than 0.35 (very excellent)
[0221] B: 0.35 or more and less than 0.50 (good)
[0222] C: 0.50 or more and less than 0.65 (level without problems in the present invention)
[0223] D: 0.65 or more (unacceptable in the present invention)
[0224] <Evaluation 3>
[0225] Evaluation paper that has been placed in a high temperature and high humidity environment (30°C, 80% RH) for more than 48 hours and fully absorbed moisture was used, and printing was performed in a high temperature and high humidity environment. The image forming device used was the device after evaluation 1-3. The image used was a halftone image of an isolated dot, and the dot reproducibility was evaluated according to the following judgment criteria:
[0226] A: Reproduce the points faithfully.
[0227] B: A slight change in the dot size can be visually observed.
[0228] C: A small change in the dot size can be visually observed.
[0229] D: A significant change in the dot size can be visually observed.
[0230] <Evaluation 4>
[0231] Using the device after evaluation 1-3, print an image of a lattice pattern with a line width of 3 pixels across the entire A4 size paper (print area ratio: 4%). Five points in the resulting image were randomly selected to measure the line width with a microscope VK-8500 (manufactured by Keyence Corporation). Calculate the average d (μm) of the line width of the three points after excluding the minimum and maximum values from the obtained values. The line width of 3 pixels is theoretically 127 μm. The difference L (μm) between 127 μm and the average d (μm) was used to evaluate the fine line reproducibility.
[0232] L(μm)=|127-d|
[0233] A: L is less than 10 μm.
[0234] B: L is 10 μm or more and less than 15 μm.
[0235] C: L is 15 μm or more and less than 20 μm.
[0236] D: L is 20 μm or more.
[0237] [Examples 2 to 18 and Comparative Examples 1 to 4]
[0238] The evaluation results are shown in Table 2.
[0239] [Table 1]
[0240]
[0241] In the table, *1 indicates the added amount of the inorganic fine particles relative to 100 parts by mass of the binder resin.
[0242] *2 indicates the addition amount of the inorganic fine particles relative to 100 parts by mass of the toner particles before heat treatment.
[0243] [Table 2]
[0244]
[0245] The present invention is not limited to the above-described embodiments, and changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, the following claims are intended to disclose the scope of the present invention.
[0246] This application claims the benefit of Japanese Patent Application No. 2018-226712, filed on December 3, 2018, which is hereby incorporated by reference herein in its entirety.
Claims
1. A white toner comprising white toner particles containing a binder resin, a white pigment, and inorganic fine particles, It is characterized in that The white pigment and the inorganic fine particles are contained in the white toner particles, The inorganic fine particles include particles dispersed in the interior of the white toner particle, wherein the interior of the white toner particle corresponds to a region on the center side greater than 0.50 μm from the surface of the white toner particle, The work function of the white pigment is 5.80 eV or more and 6.10 eV or less, The content of the white pigment is 15.0 parts by mass or more and 60.0 parts by mass or less relative to 100 parts by mass of the binder resin, and The work function of the inorganic fine particles is 6.15 eV or more. 2 . The white toner according to claim 1 , wherein the white pigment is a white pigment selected from the group consisting of titanium oxide fine particles, calcium carbonate fine particles, zinc oxide fine particles, aluminum oxide fine particles, aluminum hydroxide fine particles, and magnesium oxide fine particles. 3 . The white toner according to claim 1 , wherein the inorganic fine particles are silica fine particles. 4 . The white toner according to claim 1 , wherein the inorganic fine particles are contained in an amount of 0.1 parts by mass or more and 15.0 parts by mass or less relative to 100 parts by mass of the binder resin.
Citation Information
Patent Citations
Toner for developing electrostatic charge image, developer for electrostatic charge image, toner cartridge, process cartridge, image forming method and image forming apparatus
JP2012128008A
Electrostatic charge image developing toner
CN107807500A
Electrostatic charge image developing white toner, manufacturing method thereof, image forming apparatus, and image forming method
CN107885051A
White toner for electrostatic charge image development and image forming method
CN108803269A
